2006
DOI: 10.1080/08856250600600950
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of factors affecting the process of integration in Greek nursery schools

Abstract: In the past ten years, the issue of inclusion has proved one of the biggest challenges facing special needs education planners and policy-makers in developed countries. Greek educational policy has given emphasis on two points: (a) the development of new organizational structures (i.e. resource rooms, support teachers), and (b) the implementation of administrative regulations that enable mainstreaming special and ordinary education into a unified educational system (inclusion). In doing so, the content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
5
Order By: Relevance
“…The accounts presented here suggest that children with disabilities often exhibited low attention, adopted passive roles and displayed behaviours unrelated to the goals of the tasks set. Such divergent behaviours were also reported in another Greek study by Barbas et al (2006) in which children with disabilities in regular preschools engaged minimally with the activities set. Nevertheless, the absence of any other rigorous studies in Greece on this issue means that such conclusions should be treated with caution.…”
Section: Discussionmentioning
confidence: 55%
“…The accounts presented here suggest that children with disabilities often exhibited low attention, adopted passive roles and displayed behaviours unrelated to the goals of the tasks set. Such divergent behaviours were also reported in another Greek study by Barbas et al (2006) in which children with disabilities in regular preschools engaged minimally with the activities set. Nevertheless, the absence of any other rigorous studies in Greece on this issue means that such conclusions should be treated with caution.…”
Section: Discussionmentioning
confidence: 55%
“…The type of typically developing students’ attitudes towards students with intellectual disabilities, which are developed in a school environment, seems to be shaped by a combination of factors. The significant factors are the functionality of the disabled student (De Laat, Freriksen and Vervloed, 2013), the age (De Boer, Pijl and Minnaert, 2012), the gender (Bossaert, Colpin, Pijl et al, 2011), the family culture of the typically developing students (Morton and Campbell, 2008; Vignes, Godeau, Sentenac et al, 2009), and the frequency and quality of the social interaction between typically developing students and students with disabilities as determined by peer culture (Barbas, Birbili, Stagiopoulos et al, 2006; Hess, 2010). Finally, the dominant school culture is deemed to be the most decisive factor in the development of attitudes towards students with intellectual disabilities by their peers.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers observed a lack of support services, while the staff had no training on issues related to special education and early intervention. In a more recent study (Barbas, Birbili, Stagiopoulos, & Tzivinikou, 2006), it was found that children with disabilities experienced significant difficulties in their interactions with peers during joint class activities. However, their degree of involvement in learning activities was influenced largely by their teachers’ attitudes toward inclusive education as well as the type, nature, and quality of the strategies teachers used.…”
Section: Introductionmentioning
confidence: 99%